مخاطر استخدام طلاب المرحلة الثانوية لمواقع التواصل الاجتماعي وطبيعة سلوكياتهم فيها من وجهة نظر معلميهم بتعليم القريات في المملكة العربية السعودية - الشراري، مسند مياح سالم; الشمايلة، زيد محمود محمد (جامعة الأزهر - كلية التربية, 2020)
The present study aimed to identify the risks of secondary school students using social media from Qurayyat teachers’ viewpoints in the Kingdom of Saudi Arabia. The study made use of the the descriptive method and adopted a questionnaire for collecting the study data. The study was administered to a sample consisting of 295 teachers and the study instrument was administered to 288 during the second semester of the academic year 2019/2020. The results of the study indicated that the general level of risks resulting from the use of high school students for social media from the secondary school teachers’ viewpoints in Qurayyat adminsitration was high. The results of the study also showed that the most dangerous social networking sites was Twitter and this site was ranked first (4.085 statistical mean), and in the second rank came WhatsApp (4.030 statistical mean), and in the third rank came YouTube (4.019 statistical mean). In fourth place came Snapchat website (3.996 statistical mean) and in the fifth ranking came Instagram (3.256 statistical mean). Finally, and in the last rank came "Face Book" (3.514 statistical mean). The results of the study indicated that the general level of deviant behavior among high school students through social media sites from the viewpoint of secondary school teachers for boys in Qurayyat administration came at an intermediate level.
هدفت الدراسة بيان المخاطر المترتبة على استخدام طلبة المدارس الثانوية لوسائل التواصل الاجتماعي من وجهة نظر المعلمين بتعليم القريات في المملكة العربية السعودية، وتم استخدام المنهج الوصفي مع الاعتماد على الاستبانة في جمع البيانات، وطبقت الدراسة على عينة تكونت من 295 معلماً حيث تم تطبيق أداة الدراسة على 288 معلماً خلال الفصل الدراسي الثاني من العام الدراسي 2020/2019م، وأشارت النتائج إلى أن المستوى العام للمخاطر المترتبة على استخدام طلبة المدارس الثانوية لوسائل التواصل الاجتماعي من وجهة نظر معلمي المدارس الثانوية للبنين في إدارة تعليم القريات قد جاءت بمستوى مرتفع، كما بينت النتائج أن أكثر مواقع التواصل الاجتماعي خطورة على طلبة المرحلة الثانوية من وجهة نظر معلمي المرحلة الثانوية للبنين في إدارة تعليم القريات قد تمثلت في موقع تويتر Twitter وقد حقق هذا الموقع الترتيب الأول من حيث الأهمية بمتوسط حسابي (4.085)، وفي الترتيب الثاني موقع الواتس آب Whats App بمتوسط حسابي (4.030)، وفي الترتيب الثالث موقع يوتيوب YouTube بمتوسط حسابي (4.019). وفي الترتيب الرابع الفقرة موقع سناب شات Snap chat بمتوسط حسابي (3.996(. وفي الترتيب الخامس وقبل الأخير موقع "نستغرام Instagram" بمتوسط حسابي (3.256) وبمستوى متوسط. وفي الترتيب السادس والأخير موقع "لفيسبوك Face Book" بمتوسط حسابي (3.514)، وأشارت نتائج الدراسة إلى أن المستوى العام لمظاهر السلوك المنحرف لدى طلبة المدارس الثانوية عبر مواقع وسائل التواصل الاجتماعي من وجهة نظر معلمي المدارس الثانوية للبنين في إدارة تعليم القريات جاءت بمستوى متوسط.
Keywords: طلبة المرحلة الثانوية -- التواصل الاجتماعي -- المواقع الإلكترونية -- الاتجاهات السلوكية -- السعودية